Real-time analysis during the course of the game and its impact on the offensive skill performance and the result of the team football - Hamood Mawlood, Dhiaa; Selman Saleh, Ahmed; Khudhair Abbas, Basim (International Journal of Psychosocial Rehabilitation, 2020)
Football has now become more effective and attractive through the high progress of the arts of play. Through the observations of the researchers for some international, continental, and local matches, there are some fundamental mistakes made by the attacking player, namely individual mistakes in decision-making, which reflect this mistake on the outcome of the game, which negatively affects the team. And through the observation of researchers of the world leagues, it was noted that there are modern methods used by the training staff of the team using the devices (Tab) linked the Internet through which to follow the players the fieldand by returning the mistakes made by the player during the game, mistakes is determined by the team training staff and this player who makes mistakes that cause The weakness points in the team with another player: This mistake is explained by watching this analysis of mistakes by the training staff through the devices (tab) and noting these mistakes by the substitute player. The researchers conducted this research on some clubs of the Iraqi Premier League for advanced football players whose matches are transmitted directly in satellite channels, namely clubs (police, students, and air force), and have been monitoring all the matches that were fought in the Iraqi League for the year 2019-2020 in the Stadium of the People of the States in order to provide search requirements for the Internet.